Transcriptomic responses of beet to infection by beet mild yellowing virus - Puthanveed, Vinitha; Sajeevan, Radha Sivarajan; Siddique, Abu Bakar; Alexandersson, Erik; Joshi, Pratikshya; Snell, Per; Lennefors, Britt-Louise; Kvarnheden, Anders (BMC plant biology, 2025)
Background Virus yellows (VY) disease of sugar beet is caused by a complex of aphid-transmitted viruses, including beet mild yellowing virus (BMYV). Neonicotinoids have been used for preventing VY through aphid management, but with the recent ban on neonicotinoids in Europe, the risks for outbreaks of VY have increased dramatically. To study the host responses to BMYV infection and identify the differentially expressed genes (DEGs), we conducted an RNAseq experiment using a resistant genotype of wild beet and a susceptible breeding line of sugar beet. The experiment contained four plant treatments: exposure to aphids with or without BMYV, only insecticide spray and untreated control. Leaves were collected for analyses at 0, 1, 4, 14, 21 and 28 days post-inoculation (DPI). Results Following BMYV inoculation, resistant plants did not show any chlorosis even at 28 DPI, whereas susceptible plants displayed typical virus symptoms. Using RT-qPCR, BMYV was detected already at 1 DPI in both genotypes. At 14, 21 and 28 DPI, the virus titre in young and inoculated leaves of the susceptible genotype was higher. RNAseq revealed more DEGs as a response to BMYV infection for the susceptible genotype. In inoculated leaves, the number of DEGs increased faster for the susceptible genotype, while in young leaves, the trend was similar for susceptible and resistant genotypes. This shows that the plant responses in inoculated leaves to virus infection appeared at a larger scale in the susceptible genotype. Seven of the significantly upregulated genes in the resistant genotype encoded proteins involved in protein processing in the ER. This could be one mechanism contributing to the absence of symptoms in this genotype. Conclusions This study offers new insights into the transcriptomic events and genetic pathways regulating the defence response to BMYV in a partially resistant genotype. We present 14 candidate genes for partial resistance to BMYV and one of the possible mechanisms contributing to reduced virus levels and absence of symptoms. The findings will be of importance for future functional studies to understand the mechanisms of resistance and susceptibility as well as for the breeding of BMYV resistance.